The influence of orthodontic treatment period using the standard edgewise fixed device on the resorption of the top of alveolar bone in canines region, mandible second premolar, and first molar - Nauli, Jessy; Thahar, Bergman; Salim, Jono; Mardiati, Endah (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2014)
Orthodontic treatment could influence alveolar bone height. The longer the treatment, the more effect it will be. The purpose of this study was determined the differences in alveolar bone height at the canine, second bicuspid, mandibular first molar in the case of mandibular premolar extraction with different treatment duration. This study is a retrospective â comparative analytic study, involving 17 samples which have finished orthodontic treatment at FKG Unpad PPDGS orthodontic clinic. The alveolar bone height was determined from panoramic x-rays obtained by measuring the ratio of alveolar crest and the cemento enamel junction to the tooth cusp (Bjorn method). The results of the study were then analyzed using t-student test with Pvalue=0.05, showed a significant correlation in alveolar bone height reduction. In the group less than 2-years treatment, there was a reduction in alveolar bone height only at the mesial side of tooth 35 while there was a significant reduction at the distal canine, the mesial-distal second bicuspid and the mesial-distal side of the mandibular first molar in a group more than 2 years-treatment. This study concluded that there was a significant influence on the duration of treatment and alveolar bone height reduction in the group more than 2-years treatment.